Antihypertensive Effects of Ethanol Stem-Bark Extract of Morinda Citrifolia in Rats - Umaru, Isaac John; Okwori, Ameh Godwin; Ngbede, Ocheifa Mathew; Abdulrasheed, Lubabatu; Iseko, Kingsley Iyoko; Akafa, Tensaba Andes (Darul Yasin Al Sys, 2025)
The medical term used for blood pressure is Hypertension (HTN). Hypertension is a common problem faced by most people today. The leading danger for many diseases such as CVD (cardiovascular) disorder and stroke is high blood pressure. Major diseases like CHF (congestive heart failure), renal disease and blindness can also be caused by HTN. Awareness of plant-based medication therapeutics is continuously increasing day by day. Morinda citrifolia L (Noni) has been used in folk remedies by Polynesians for over 2000 years, and is reported to have a broad range of therapeutic effects. The purpose of this study is to investigate the hypotensive potential of Morinda citrifolia L (Noni) (Family: Rubiaceae) in both normotensive and hypertensive rats. Methods: Aqueous-methanol (70:30) extract of Morinda citrifolia L stem-bark extract at doses of 25, 50, 75 and 100 mg/kg was evaluated for its effect on blood pressure and heart rate using non-invasive blood pressure measuring apparatus. After initial screening, 100 mg/kg dose that produced a maximum effect was selected for the antihypertensive study. Median lethal dose (LD50) and sub-chronic toxicity of the extract were also determined. Various biochemical parameters and organ weight were measured using standard procedures. Results: The extract produced a significant (p < 0.01) decrease in systolic blood pressure (SBP), mean blood pressure (MBP), diastolic blood pressure (DBP) and heart rate of normotensive rats at all test doses with maximum effect at 100 mg/kg. Similarly, a significant antihypertensive and negative chronotropic effect was observed in both hypertensive models. LD50 of the extract was 200 mg/kg in mice. The extract also exhibited a reduction (p < 0.05) in serum alanine transaminase (ALT), aspartate aminotransaminase (AST), alkaline phosphatase (ALP), triglycerides and low-density lipoprotein (LDL) levels while a significant (p < 0.05) increase in high density lipoproteins (HDL) level was observed. Conclusion: It seems that the aqueous-methanol stem-bark extract of Morinda citrifolia L possesses active compounds which may be responsible for the antihypertensive and negative chronotropic effects in rats.